TATA KELOLA KEMITRAN CORPORATE SOCIAL RESPONSIBILITY PT SEMEN TONASA DALAM PENYEDIAAN AIR BERSIH DI DESA BIRING ERE TONASA II KABUPATEN PANGKEP - Sri Fajriani; Fatmawati Fatmawati; Abdi Abdi (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2020)
This research purposed to find out how the partnership management in the provision of clean water at Biring Ere village, Pangkep Regency. This research used qualitative research with the type descriptive research. The number of informants in the study was 7 people. Data analysis used a qualitative research approach. The type of research used phenomenological research. Data collectiontechniques were instruments in the form of observation, interviews with informants. The data were analyzed descriptively. The results of this research showed that the partnership of the first parrty and the second party in suppling clean be seen from the utilization of clean water supply. But, the development had not been as expected due to the lack of proper maintenance that carried out by the community after post-development. But with the existence of partnersship management, it provided benefits for the community in Biring Ere Village, Pangkep Regency.